Geochemical and isotope characteristics of representative carbonates in young alkaline volcanites from northern Bohemia - Ulrych,J.; Pivec,E.; Povondra,P.; Bendl,J. (Journal of the Czech Geological Society, 1997)
Carbonates of young alkaline volcanics from northern Bohemia have carbon of primary magmatic character with a shift to light isotopes, in association with fractionation processes. The oxygen isotopes show equilibration with meteoric - hydrothermal water at low temperatures. Representative samples reveal the following characteristics: - dolomites associated with melilititic lamprophyres - polzenites of the Osecna Complex are characterized by high REE, high La/Yb ratio, and by δ13C values in the primary magmatic range (carbonatite affinity), but with δ18O values and 87Sr/86Sr ratios corresponding to lower-temperature processes and some crustal contamination - calcites in phlogopitite, originated as alteration product of olivine melilitolite of the Osecna complex by late-magmatic fluids, are characterized by very low REE, low La/Yb ratio, low δ13C values and by 87Sr/86Sr ratio corresponding to the parental rock; high δ18O values indicate lower-temperature origin - calcites from the contact zone of polzenite dyke with sandstones of the Czech Cretaceous Basin, with geochemical characteristics typical for sedimentary origin, are characterized by low REE, low La/Yb ratio and very high δ13C, δ18O values, and 87Sr/86Sr ratios - rhodochrosite-dolomite-calcite series of post-magmatic hydrothermal origin, associated with base metal ore vein in the Roztoky Volcanic Centre of the Ceske stredohori Mts., is characterized by moderate REE contents and Yb/La ratios, high Sr and Ba contents and by 87Sr/86Sr ratio reflecting some crustal contamination; δ13C values indicate probably minor admixture of sedimentary C in carbon of deep-seated origin, while the O isotope data point to participation of a low δ18O fluid of meteoric derivation.
Keywords: carbonates; volcanism; geochemistry; C; O; Sr isotopes